Cavitation behavior of polypropylene/polyethylene multilayer films during uniaxial tensile deformation: In-situ synchrotron X-ray study. (16th January 2023) - Chen, Zhenxian; Xiong, Bijin; Li, Zhao; Yao, Kun; Li, Xuke
Abstract: The cavitation of melt-coextruded multilayer films of alternated polypropylene (PP) and polyethylene (PE) during the uniaxial tensile deformation has been investigated. The initiation and evolution of cavities and the relationship between cavitation and plastic deformation have been studied via in-situ SAXS and WAXS techniques. The critical strain for the initiation of cavitation ( ε cav ), crystal shear ( ε CSh ), and yield ( ε yield ) have been estimated from the in-situ experiments. The results show that the sequence of deformation is crystal shear, cavitation and yield, i.e. ε CSh< ε cav< ε yield, indicating that crystal plastic deformation occurs before the cavitation and yield. Additionally, the layer numerosity and annealing temperature ( T a n n e a l ) have been discovered to not only modify the mechanical behavior but also regulate cavitation by changing the initial microstructure. The samples with less layer numerosity and high T a n n e a l improve the macroscopic mechanical strength, whereas the increase of layer numerosity can reduce the stress of cavitation onset ( σ cav ) and retard the onset of cavitation onset (high ε cav value). The current study is significant in elucidating the internal mechanism of stretch-induced cavitation behavior in multilayer films. Graphical abstract: Image 1 Highlights: Cavitation of multilayer films during uniaxial tension has been investigated via in-situ X-ray scattering. Sequence of deformation, including crystal shear and cavitation and yield, has been observed. Layer numerosity and annealing temperature have been discovered to modify both mechanical behavior and cavitation.